IMPLEMENTATION OF THE GOVERNMENT'S DISCRETION IN INDONESIA, AUTHORITY, AND RESPONSIBILITY IN THE MANAGEMENT OF GOVERNMENT - Nur Ro`is; Tri Yani; Putri Mayang Sari; Dewi Ary Nurdiana Putri; Lupi Mardiansyah (JURNAL DINAMIKA, 2021)
The research entitled "Implementation of the Government's Discretionary Authority and Accountability in the Administration of Government" has five problem formulations. First, how is the implementation of discretionary authority in the administration of Government? Second, there are obstacles in the exercise of discretionary authority. The third is how to overcome obstacles. Fourth, the limits of discretion in decision making. Fifth, Government Instruments. The purpose of this study was to identify and analyze the five problem formulations above. This research is qualitative descriptive The results of this study indicate that the exercise of discretionary authority in the administration of Government is a logical consequence of the welfare state where the welfare state government is a state power that is given the task and responsibility for the welfare of its citizens. In contrast, discretionary authority does not mean that it can be used freely. However, it must follow the rules written in Law Number 30 of 2004 concerning Good Governance and Principles of Good Governance (AAUPB). The implementation of discretionary authority in the administration of Government also has several obstacles that cause the Government to be less efficient and less effective. Efforts to overcome these obstacles are not easy because they must involve all parties, namely legislative power, executive power, and judicial power. This is also, of course, requires the role of citizens. These things are to ensure the implementation of discretionary authority in the administration of Government so that it is efficient and effective in realizing people's welfare.